Identification of a CE-SDS shoulder peak as disulfide-linked fragments from common CH2 cleavages in IgGs and IgG-like bispecific antibodies. Issue 1 (1st January 2021) - Cao, Mingyan; Jiao, Yang; Parthemore, Conner; Korman, Samuel; Ma, Jiao; Hunter, Alan; Kilby, Greg; Chen, Xiaoyu
ABSTRACT: Fragmentation is a well-characterized degradation pathway of therapeutic antibodies and is usually monitored by capillary electrophoresis–sodium dodecyl sulfate (CE-SDS). Although fragments due to cleavage in CH 2 domains linked by intrachain disulfide bonds are common and can be detected by reduced reversed-phase – liquid chromatography mass spectrometry (RP-LCMS) and reduced CE-SDS methods, their separation in nonreduced CE-SDS (nrCE-SDS) has not been reported but speculated as comigrating with intact IgG. A shoulder peak in nrCE-SDS was observed in the stability samples of an IgG-like bispecific antibody and was determined to be mainly caused by fragments from clipping at the C-terminus of leucine (L)306 or L309 (EU numbering) in the CH 2 domain of both heavy chains (HCs) and, to a lesser degree, at the C-terminus of L182 in the CH 1 domain of the knob HC. Subunit LCMS analysis verified that the crystallizable fragment contained variants with one or multiple mass additions of 18 Da due to clipping. Further investigation revealed that CH 2 clippings at L306 and L309 were largely due to proteolytic activity, and cleavages were present at various levels in all in-house IgG1 and IgG4 molecules studied. Our study shows that CH 2 domain cleavages, with complementary fragments still linked by intrachain disulfide, can be electrophoretically resolved as a front shoulder of the main peak in nrCE-SDS. Given the high occurrence of CH 2 cleavages in antibodies, these findings will have broad applicability and could help manufacturers of therapeutic antibodies in process improvement, product characterization, investigations, formulation stability, and stability comparability studies.